Pengaruh Implementasi Metode Diskusi Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran PAI Kelas X Otomatisasi &Tata Kelola (OTKP) Di SMK Ciledug Al-Musaddadiyah Garut - Raito, Raito; Agustin, Sopia (STAI Al-Musaddadiyah Garut, 2022)
Critical thinking is essential for students to cultivate, as it enables them to harness their potential to identify, comprehend, and solve problems. However, critical thinking has not yet become a prevalent culture among students. This may be due to the insufficient use of teaching methods that encourage critical thinking, particularly in Islamic Religious Education (PAI) classes. PAI is a subject that imparts knowledge and shapes students' attitudes, personalities, and skills in practicing religious teachings, which are integrated across all educational levels and types. The discussion method in PAI is adapted to address issues that can be resolved collaboratively, with each student expressing their opinions. This method can significantly foster critical thinking among students. This research employs a quantitative inferential approach, collecting data or information about the phenomena under study. Data collection techniques included distributing questionnaires to 25 respondents, conducting classroom observations in Class X OTKP to observe the learning process, and document analysis. Data processing was carried out using statistical analysis. The statistical tests revealed that the discussion method in PAI subjects contributes 19.48% to the development of students' critical thinking skills. In contrast, 80.52% of the factors influencing critical thinking were attributed to other variables not examined in this study. Keywords: Implementation of Discussion Method, Critical Thinking Skills, Islamic Religious Education